Osseointegration of a displaced dental implant in the maxillary sinus: a 7-year follow-up case report - Azenha, Marcelo Rodrigues; Watanabe, Plauto Cristopher Aranha; Errázuriz, Sebastián Pérez; Jardim, Luis Fernando; Sório, Ana Luisa Riul (Brazilian Journal of Case Reports, 2024)
Foreign bodies into the maxillary sinus are rarely mentioned in literature. Many of them might be asymptomatic and an inadequate planning of the case or an unskilled professional can easily lead a dental implant into the maxillary sinus in a poor bone situation. We aim to present and discuss what is to our knowledge the first case and the management of a dental implant that has osseointegrated inside the maxillary sinus after its displacement. A patient had a dental implant placed immediately after upper molar extraction, but at the end of the procedure it was displaced into the sinus during healing cap adaptation. Images exams done after 1 day, 24 months, 36, and 84 months demonstrated a healthy maxillary sinus with the implant osseointegrated at the same site since its migration, surrounded and filled by mature bone. Due to an asymptomatic patient the removal of the implant is not planned until now.